The Alkane Hydroxylase Gene of Burkholderia cepacia RR10 Is under Catabolite Repression Control - Marín, Mercedes M. (American Society for Microbiology, 2001)
In many microorganisms the first step for alkane degradation is the terminal oxidation of the molecule by an alkane hydroxylase. We report the characterization of a gene coding for an alkane hydroxylase in a Burkholderia cepacia strain isolated from an oil-contaminated site. The protein encoded showed similarity to other known or predicted bacterial alkane hydroxylases, although it clustered on a separate branch together with the predicted alkane hydroxylase of a Mycobacterium tuberculosis strain. Introduction of the cloned B. cepacia gene into an alkane hydroxylase knockout mutant of Pseudomonas fluorescens CHAO restored its ability to grow on alkanes, which confirms that the gene analyzed encodes a functional alkane hydroxylase. The gene, which was named alkB, is not linked to other genes of the alkane oxidation pathway. Its promoter was identified, and its expression was analyzed under different growth conditions. Transcription was induced by alkanes of chain lengths containing 12 to at least 30 carbon atoms as well as by alkanols. Although the gene was efficiently expressed during exponential growth, transcription increased about fivefold when cells approached stationary phase, a characteristic not shared by the few alkane degraders whose regulation has been studied. Expression of the alkB gene was under carbon catabolite repression when cells were cultured in the presence of several organic acids and sugars or in a complex (rich) medium. The catabolic repression process showed several characteristics that are clearly different from what has been observed in other alkane degradation pathways.